Hubungan Tingkat Pengetahuan dan Kepatuhan Setelah Pemberian Brief Counseling Terhadap Luaran Klinik Pasien Hipertensi - Monia Agni Wiyatami; Nanang Munif Yasin; Ika Puspita Sari (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Uncontrolled hypertension is a major health problem in society, so that a good knowledge and adherence are needed to achieve controlling of blood pressure targets. This study aimed to determine correlation between knowledge level and adherence after provided brief counseling by pharmacist to clinical outcomes of prolanis hypertension patients. The study design was a quasi-experimental pretest and posttest with a control group. The form of intervention is brief counseling using poster and follow-up via whatsapp or telephone for hypertension patients who are prolanis participants that entered inclusion criteria with blood pressure > 140/90 mmHg. The study was carried out during September–December 2021 in 6 public health centers in Pangkalpinang city, such as 3 for intervention (kacang pedang, gerunggang, pasir putih) and 3 for control group (melintang, air itam, taman sari). The sample total was 90 peoples, consist of 46 intervention groups and 44 control groups. The data were collected by interviews using questionnaire of Hypertension Knowledge Level Scale (HK-LS) and Morisky Green Levine Scale (MGLS), the clinical outcomes using blood pressure data taken from medical records. Correlation between knowledge level and adherence to clinical outcomes have been analyzed using the Rank Spearman correlation test. The results showed that there was a correlation between changes the level of knowledge on systolic (p=<0,001; R value -0.374) and diastolic (p=0.001; R value -0.349) declines, and also there was a correlation between changes in adherence to systolic decline (p=0.046; R value of -0.211). However, there was no significant correlation between changes in adherence to diastolic decline (p=0.063). From this study it was concluded that there was a significant correlation between the level of knowledge and adherence after provided brief counseling by pharmacist to clinical outcomes of prolanis hypertension patients.